The role of caregiver burden as a predictor of anxiety among families of hospitalized patients with cardiovascular disease - Zannuba Aulia Maghfiroh; Nanda Audia Vrisaba (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Family members accompanying hospitalized patients with cardiovascular disease often face significant stress during the care process. The demands of providing care, understanding medical information, making decisions, and coping with the uncertainty of the patient's condition can lead to caregiver burden and increase the risk of anxiety. Purpose: To determine the role of caregiver burden as a predictor of anxiety among family members of hospitalized patients with cardiovascular disease. Method: This study employed a quantitative approach with a cross-sectional design. Participants consisted of 113 family members of hospitalized patients with cardiovascular disease. Caregiver burden was measured using the Zarit Burden Interview (ZBI-22), while anxiety was assessed using the Generalized Anxiety Disorder scale (GAD-7). Data were analyzed using linear regression to determine the role of caregiver burden in predicting anxiety. Results: Linear regression analysis showed that caregiver burden served as a significant positive predictor of anxiety among family members of patients with cardiovascular disease (B = 0.240; β = 0.728; t = 11.202; p < 0.001; 95% CI = 0.198–0.283). An R² value of 0.531 indicated that caregiver burden accounted for 53.1% of the variance in anxiety among the patients' family members. Conclusion: Caregiver burden plays a significant role in increasing anxiety among family members of hospitalized patients with cardiovascular disease. The greater the burden perceived by the family while caring for the patient, the higher the level of anxiety experienced. These findings highlight the importance of addressing caregiver burden as an integral part of holistic healthcare services. Suggestion: Future research should expand the study location to include more than one hospital or an entire region, so that the findings can more broadly reflect the situation of cardiovascular patient caregivers. Keywords: Anxiety; Caregiver Burden; Cardiovascular Disease.